Chemical profiling of maize volatiles based on retention characteristics and dependent emission patterns of healthy, oviposition-induced and herbivore-induced plant volatiles affected by fall armyworm Spodoptera frugiperda (J.E. Smith) - Amit, K; Ramesh, B S; Shanti, M; Ramya, A R; Murugan, M; Srinivasan, T; Suganthi, A; Anuradha, P; Muralitharan, V; Beerendra, S (Plant Science Today, 2026)
Maize (Zea mays L.) is a critically important global cereal crop, the productivity of which is increasingly threatened by the invasive fall armyworm, Spodoptera frugiperda. In response to herbivory, plants deploy indirect defences by emitting herbivore-induced plant volatiles (HIPVs), which can attract natural enemies of the pest. This study investigated the volatile organic compound (VOC) profile of maize plants under three conditions: healthy, oviposition-induced and herbivore-induced by S. frugiperda. Using gas chromatography mass spectrometry (GC-MS), we identified and quantified 11 key VOCs across 6 chemical classes. The results revealed significant qualitative and quantitative differences in the volatile profiles among the treatments. Key compounds included the aldehydes pentanal (2,2-dimethyl) and nonanal; the ketone 1-(3-ethyloxiranyl) ethanone; the alcohol 3-buten-2-ol; several esters, most prominently oxalic acid, cyclohexyl propyl ester; and the terpenes d-limonene and β-caryophyllene. The distinct emission patterns of these VOCs, particularly the significant changes in specific terpenes and green leaf volatiles (GLVs), provide crucial insights into the chemical ecology of maize defence against S. frugiperda. These findings suggest that induced volatile blends could play a role in tritrophic interactions and offer a foundation for developing sustainable pest management strategies based on plant signalling.